Oil Palm Plantation Development Policy in Riau Province: An Overview of The Political Economy - Auradian Marta; Leo Agustino; Utang Suwaryo; Affan Sulaeman (JURNAL ILMU SOSIAL, 2018)
This study discusses why the impact of the policy of developing oil palm plantations by corporations in Riau Province is not felt fairly and equally by the community. This study uses a qualitative approach and meta-analysis with data sources from books, scientific journals, and mass media. Data is analyzed by interactive methods and supported by theory. The results of this study indicate that neoliberalism has had an influence on the policy of developing oil palm plantations in Riau Province. This neoliberalism practice can be seen from the policy of the development of oil palm plantations in Riau which are more impartial and benefit the corporation or the owners of capital than the people around the plantation area. This can occur because of the dominance of companies and corporations in relation to the regional government. Bribery is the way they use if the lobbies made against politicians and government officials have not succeeded in achieving the goal. The state becomes subordinate in its relations with the corporation, so what happens is corporate hegemony in the development of oil palm plantations in Riau Province.